(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The research work reflects some basic indicators of the water regime. Experimental researches were carried out on five varieties of soybean (Glycine max. (L.) Merr.), cultivated on gray soil of the Chui Valley (Kenesh village). During several seasons, research has been carried out to study the water-holding capacity, the intensity of leaf transpiration and the water content in the leaves of various soybean varieties. We determined the daily dynamics of transpiration intensity, its minimum and maximum values for domestic and foreign soybean varieties. It was revealed that the IT of leaves has a one- and two-peak curve, where its maximums were observed at 3 and 5 o’clock in the afternoon at air t +33-35°C. Based on the water content in the leaves and the ability to retain water, the indicators of all samples remain in high concentrations for up to half a day. But with the increase in temperature and its decrease in the evening, a smooth decline is observed on the graph. Despite the arid climate of the northernmost region of the country, the conditions of the Chui Valley allow the cultivation of soybean varieties. The results obtained describe their resistance to atmospheric and soil drought.